Muatan Materi Sejarah Lokal Dalam Pembelajaran Sejarah (Studi Kasus di SMA N 3 dan SMA N 6 Pontianak) - Andang Firmansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The principle of learning history is learning that teaches students to emulate heroic values. During this, history learning is more than memorizing without knowing the meaning behind the event. Heroic values are often ruled out and not understood in-depth by their students. Moreover, local hero figures are less raised in learning material. As a result, little local historical material is conveyed, and even then depends on the resources available at the school. Based on research conducted in SMA N 3, Pontianak has included local history material, while in SMA N 6, Pontianak has not included it, even though both schools have implemented the 2013 Curriculum. This disparity occurs due to a lack of sources and teaching materials that contain local historical material. Therefore in the future, the writing of teaching materials based on local history material that uses credible and accurate sources must be done so that learning history can be more creative and innovative.